사라지는 버스터미널의 지역문화자원으로서의 활성화 방안 연구 - 이진욱(Jin-Wook Lee); 노영희(Younghee Noh); 이상엽(Sang-Yup Lee); 이지현(Ji-Hyun Lee); 이명주(Myoung Joo Lee) (한국비교정부학보, 2024)
(Purpose) The increasing risk of regional extinction due to population decline can be directly linked to the reduction of local cultural resources. This study was conducted to analyze the current status of bus terminals, a cultural resource at risk of disappearance, and to consider revitalization strategies amidst the challenges of population decline. (Design/methodology/approach) The study focuses on the phenomenon of closures of intercity and express bus terminals driven by population decline and the expansion of alternative transportation methods. It assesses the impact of these closures on local communities and the transportation industry. Particularly, it examines terminal closure cases from 2018 to 2023 to establish a direct correlation between decreasing population and declining user numbers. (Findings) Based on the analysis, this research proposes three strategic approaches. First, actively developing tourism resources to increase the inflow of people into the region. This strategy involves not only developing tourism resources but also linking these resources with bus terminals to ensure that tourists utilize these facilities. Second, transforming bus terminals into integrated transportation hubs through connections with urban transit systems and nearby airports, and further developing these hubs into complexes that attract populations in conjunction with commercial districts. Third, utilizing the existing facilities of bus terminals to extend beyond mere human transportation to possibly include goods transportation functions as well. KCI Citation Count: 3